2016
DOI: 10.1016/j.ejor.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

The effects of integrating management judgement into OUT levels: In or out of context?

Abstract: Physical inventories constitute a significant proportion of companies' investments in today's competitive environment. The trade-off between customer service levels and inventory reserves is addressed in practice by statistical inventory software solutions; given the tremendous number of Stock Keeping Units (SKUs) that contemporary organizations deal with, such solutions are fully automated. However, empirical evidence suggests that managers habitually judgementally adjust the output of such solutions, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 42 publications
0
18
0
2
Order By: Relevance
“…Despite a large number of publications, for example [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]20] which are devoted to efficiency or optimization criteria development, indicators that are based on all objects of the full global operation model are practically absent.…”
Section: Efficiency Formulamentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a large number of publications, for example [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]20] which are devoted to efficiency or optimization criteria development, indicators that are based on all objects of the full global operation model are practically absent.…”
Section: Efficiency Formulamentioning
confidence: 99%
“…Increase of business development's rates is closely connected with a possibility of the perceived and objective choice of the best way of a scenario among many possible alternatives [1][2][3]. A necessary condition of such development is value increase of operational process output products in relation to the input products value.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the authors demonstrate that by adopting simple strategies (guidance, restrictiveness, Blattberg-Hoch), the negative impacts of this behaviour can be reduced. In their article on the potential value of judgmental adjustments to statistically derived inventory related decisions, Syntetos, Kholidasari and Naim (2015) found that judgmentally adjusting order-up-to (OUT) levels offers a small advantage, and that this advantage is associated with negative adjustments, whilst larger adjustments do not perform well. In addition, the authors demonstrate that when adjustments of OUT levels are accompanied by a justification for the adjustment, then this leads to an improved inventory performance.…”
Section: Introduction To the Articles In The Special Issuementioning
confidence: 99%
“…For example, there is a stream of research that examines the work of expert modellers (Tako, 2014;Tako & Robinson, 2010;Waisel, Wallace, & Willemain, 2008;Willemain, 1994Willemain, , 1995 , novice modellers (S. G. Tavella & Papadopoulos, 2015b;, or both (Tavella & Papadopoulos, 2015a). Research focusing on other types of actors is also beginning to appear, such as studies of forecasting experts (Petropoulos, Fildes, & Goodwin, 2016;Syntetos, Kholidasari, & Naim, 2016), decision analysts (Papamichail, Alves, French, Yang, & Snowdon, 2007), and OR consultants proving strategy support (O'Brien, 2015).…”
Section: Focus On or Actorsmentioning
confidence: 99%